The teaching of the Pythagorean theorem: classroom experience with the use of geogebra according to Van Hiele model - Vargas Vargas, Gilberto (2013)
The present article has as purpose to present the results of an experience carried out with high school students with on the issue of the Pythagorean theorem and its reciprocal supported the use of GeoGebra and in the Van Hiele geometric reasoning model. For this it was designed and it implemented a methodological strategy, with twelve activities, to a group of ninth year of secondary education of Costa Rica, in the II trimester 2009, and compared the level of reasoning displayed by them with those who worked on this topic a traditional approach. The study was of qualitative type. Among the main findings highlighted that students who developed the activities supported by the GeoGebra felt more motivated to study Mathematics, especially Geometry, than those who did so under the traditional approach and the methodological strategy used in managed make many of the students who had low grades were motivated to "compete" and discuss mathematical ideas with students who had better grades than them, so that we can say that this strategy helped to strengthen their confidence in their interaction with others.